Protein malnutrition effects of perivascular bone marrow microenvironment on the regulation of hematopoiesis - Hastreiter, Araceli Aparecida (2019)
Protein malnutrition (PM) causes anemia and leukopenia by reduction of hematopoietic precursors and impaired production of mediators that induce hematopoiesis, as well as structural and ultrastructural changes in the bone marrow (BM) extracellular matrix. Hematopoiesis occurs in the bone marrow (BM) in distinct regions called niches, which modulate the processes of differentiation, proliferation and self-renewal of the hematopoietic stem cell (HSC). The perivascular niche, composed mainly by mesenchymal stem cells (MSC) and endothelial cells (EC), is the major modulator of HSC and its function extends to the migration of mature hematopoietic cells into the peripheral blood through the production of cytokines and growth factors. Thus, our hypothesis is that PM changes the perivascular niche and our objective is to evaluate whether PM affects the modulatory capacity of MSC and EC on hematopoiesis. C57BL/6 male mice were divided into Control and Malnourished groups, which received for 5 weeks, respectively, a normal protein diet (12% casein) and a low protein diet (2% casein). After this period, animals were euthanized, nutritional and hematological evaluations were performed, featuring the PM. We performed leukemic myelo-monoblasts cells transplantation and observed that these cells have a lower proliferation rate and are rather in the cell cycle G0/G1 phases in malnourished mice, indicating that the BM microenvironment is compromised in PM. MSC were isolated, characterized and differentiated in vitro into EC cells, which were evidenced by CD31 and CD144 markers. We performed the quantification of HSC and hematopoietic progenitors, as well as some regulators of proliferation and differentiation, ex vivo and after cultures with MSC or EC. We observed that PM reduces HSC and hematopoietic progenitors ex vivo. In PM, MSC promote increase in HSC and suppress hematopoietic differentiation, whereas ECs induce cell cycle arrest. Additionally, we verified that PM affects granulopoesis by decreasing the expression of G-CSFr in granule-monocytic progenitors. Thus, we conclude that PD compromises hematopoiesis due to intrinsic alterations in HSC, as well as alterations in the medullary perivascular niche.